Pendampingan Baca Tulis Al-Qur’an Dan Hafalan Surah Pendek - Andi Rahmah Alvira; A. Taufiq Nur; Takdir, Takdir (PENDIMAS: Jurnal Pengabdian Masyarakat, 2022)
One of the informal institutions in the field of religious education that is rife in the community is the Al-Qur'an Education Park. The mentoring carried out at the Babussalam Honto Al-Qur'an Education Park aims to improve the memorization of short suras and develop knowledge in reading the Qur'an. Teaching materials at the Al-Qur'an Education Park (TPA) specifically develop learning materials in providing basic knowledge, attitudes and religious skills. Especially for teaching that is less likely to be achieved completely through education in formal schools. For example, reading and writing the Qur'an, practicing prayer, memorizing verses of the Qur'an, daily prayers, planting moral beliefs, Islamic knowledge and so on.